1995
DOI: 10.1002/1097-4679(199505)51:3<448::aid-jclp2270510321>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical interventions by psychologists with lesbians and gay men

Abstract: A questionnaire that assesses methods of intervention with, and attitudes toward, lesbians and gay men was completed by 139 clinical psychologists. None claimed to use aversion techniques to change sexual orientation. Eleven percent reported use of alternative methods (e.g., psychoanalytic techniques) to change sexual orientation, whereas 5.8% supported the use of aversion therapy for this purpose. Viewing homosexuality as “unacceptable” predicted both the use of alternative therapies and support of aversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
2
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 10 publications
0
18
2
7
Order By: Relevance
“…More recent studies also suggest that the legacy of the pathological view of homosexuality continues to impact psychological treatment of LGB individuals. In a survey of clinical psychologists, although 79% reported that they viewed homosexuality as acceptable, 12.9% reported that they viewed homosexuality as a psychosexual disorder, and 5% described it as a personality disorder (Jordan & Deluty, 1995). In this same survey, 5.8% supported the use of aversion therapy to change sexual orientation, and 11% supported the use of methods such as psychoanalysis for this purpose.…”
Section: Optimismmentioning
confidence: 96%
“…More recent studies also suggest that the legacy of the pathological view of homosexuality continues to impact psychological treatment of LGB individuals. In a survey of clinical psychologists, although 79% reported that they viewed homosexuality as acceptable, 12.9% reported that they viewed homosexuality as a psychosexual disorder, and 5% described it as a personality disorder (Jordan & Deluty, 1995). In this same survey, 5.8% supported the use of aversion therapy to change sexual orientation, and 11% supported the use of methods such as psychoanalysis for this purpose.…”
Section: Optimismmentioning
confidence: 96%
“…One survey of randomly selected psychologists found that approximately 6% of respondents still advocate conversion therapy (Jordan & Deluty, 1995). Only one study to date has addressed the degree to which career counselors practice affirming approaches with gay, lesbian, and bisexual clients (Bieschke & Matthews, 1996).…”
Section: Counselor Biasmentioning
confidence: 99%
“…Moreover, some lesbigay students have reported evidence of bias or discrimination in textbooks, course materials, course content, instructor comments, research supervision, clinical practica and internships, interactions with program administrators and other faculty, teaching assistantships, and course content (Pilkington & Cantor, 1996). As a result, many mental health professionals engage in a number of harmful practices, many of which are proscribed under the ethical guidelines of their profession (Davis, Cole, & Rothblum, 1996;Garnets, Hancock, Cochran, Goodchilds, & Peplau, 1991;Jordan & Deluty, 1995;Liddle, 1996Liddle, , 1997Milton & Coyle, 1998;Trippet, 1994;Welch, 2000).…”
mentioning
confidence: 99%